Scheme Design and Data Analysis of Critical Physical Experiment for Hexagonal Casing Type Fuel Reactor - Lianjie, Wang; Yanqin, Wei; Lei, Lou; Shien, Huang (Frontiers in Energy Research, 2021)
Based on the requirement of Hexagonal Casing Type Fuel Reactor (HCTFR) nuclear design and the critical physical experiment design method introduced by single factor, 11 core critical physical experiments are proposed to validate the calculation accuracy and reliability of the nuclear design code CPLEV2. The experiment loading scheme fully takes into account the various components and more than one irradiate hole in HCTFR core, which is used as critical physical experiment schemes successfully. According to the critical physical experiment data, the reactivity calculation deviations of all critical physical experiments are within ±1.0%. The validation results show that the nuclear design code CPLEV2 has high calculation accuracy and reliability for the core of hexagonal casing type fuel and it can be used for HCTFR nuclear design.